Microbial biofilms—Development, behaviour and therapeutic significance in oral health - S Nithya; Susmita Saxena; Jitin Kharbanda (Journal of Dr. NTR University of Health Sciences, 2020)
Background: Biofilms are communities of microorganisms that are found attached to a surface. They develop on both biotic and abiotic surfaces and could act as a source of infection. The formation of biofilm involves the population of bacteria in an extracellular matrix exhibiting a cooperative group behavior. It is a dynamic process that involves adhesion, growth mobility, and extracellular matrix production with both cells and the environment contributing to the formation of this matrix material. The biofilm exhibits unique properties of protecting itself from host defenses and desiccation, persistence in the flowing system, heterogeneity, spatial organization, and resistance to antimicrobial agents through its ability to influence gene expression and phenotype. Quorum sensing, a means of a cell to cell communication is closely interconnected to the development of biofilm formation and inhibition. Dental plaque is the most common and well known oral biofilm. The preponderance of biofilm-associated diseases and its resistance in eradication has potentiated the need for further research in this field. Purpose: The purpose of this review is to create an awareness of the dentist on biofilms, its mode of formation, and the effect of biofilms on oral health. A comprehensive search of all literature on biofilms pertaining to oral health using literary search engines like PubMed and PubMed central has been taken into account in reviewing the pathogenesis and significance of biofilms in this article.